Climate change impacts on flood pulse characteristics in the Barotse Floodplain, Zambia - Mroz, E. J.; Smith, M. W.; Willis, T. D. M.; Trigg, M. A.; Malawo, H.; Chalo, C.; Sinkombo, M.; Thomas, C. J. (2025)
Tens of millions of livelihoods depend on floodplains, making them especially vulnerable to climate change. However, understanding how annual floods may change and impact local vulnerabilities remains limited. Daily precipitation and temperature projections were obtained from five CMIP6 (Coupled Model Intercomparison Project) General Circulation Models in the Inter-Sectoral Model Inter-Comparison Project (ISIMIP). These were input into a coupled hydrological-hydraulic model of the Barotse Floodplain, Zambia to obtain data on flood pulse timing, duration, and magnitude. Future decades (2030s, 2050s, 2070s) under three Shared Socio-Economic Pathways (SSPs 1–2.6, 3–7.0, 5–8.5) were compared with baseline data from the 1990s and 2000s to assess the impact of climate change. Climatic indices were also correlated with flood pulse characteristics to assess whether a driver of changes could be determined. Future floodwaves in the Barotse showed reduced durations and magnitudes, and altered timings of flood rise and recession compared to baseline periods. These differences were significant in the mid-to far-future. Large areas of the floodplain experience 1-to-2 month reductions in inundation duration, and some areas experienced no inundation in a hydrological year for the first time. The northern Barotse Floodplain, western escarpment, and Luena Valley exhibit the greatest sensitivity to future changes. The Barotse Floodplain will become increasingly arid under all climate scenarios, exacerbating existing challenges for transhumance communities dependent on floods, who face periodic food insecurity, malnutrition, and limited healthcare access. Intensified drought conditions under future climate change will undermine the resilience of local livelihoods, reflecting broader vulnerabilities faced by floodplain-dependent communities globally.